Particle Engineering by Nano Spray Drying: Optimization of Process Parameters with Hydroethanolic versus Aqueous Solutions - Khaled Almansour; Raisuddin Ali; Fawaz Alheibshy; Tariq J. Almutairi; Rakan F. Alshammari; Nasser Alhajj; Cordin Arpagaus; Mustafa M.A. Elsayed (MDPI AG, 2022)
Nano spray drying has emerged as an outstanding platform for engineering micro- and nanoparticles, with growing applications in various areas of drug delivery. As a new technology involving distinct technical design, parameters of the nano spray drying process are not fully elucidated. In a quality-by-design approach, the aim of the current study was to gain thorough understanding of critical determinants of product characteristics in the Büchi Nano Spray Dryer B-90. Following a factorial experimental design, a series of spray drying experiments were conducted to gain new insights into the influences of the inlet temperature, the spray solvent, and the solute concentration in the spray solution on the yield, the moisture content, and the particle size of the nano spray-dried powder material. Special consideration was given to the potential of using hydroethanolic in comparison with aqueous solvent systems and to particle engineering for pulmonary drug delivery. Lactose and mannitol, widely used as excipients in dry powder inhalation formulations, were used as model materials. Lactose and mannitol are known to spray dry in amorphous and crystalline forms, respectively. The yields of spray drying of lactose and mannitol amounted generally to 71.1 ± 6.6% w/w and 66.1 ± 3.5% w/w, respectively. The spray-dried materials exhibited generally a number-weighted median particle diameter of 1.6 ± 0.2 μm and a volume-weighted median particle diameter of 5.1 ± 1.0 μm. A detailed analysis of the results improved understanding of the interplay between process parameters in the Nano Spray Dryer. The results demonstrate that optimization of spray generation is the key to yield optimization. On the other hand, particle size is determined by the spray mesh pore size and the spray solution degree of saturation. Selection of an appropriate spray solvent and using spray solution additives could optimize spray flow. In parallel, the spray solvent and the solute concentration in the spray solution determine the degree of saturation. Guidance on optimization of particle engineering by nano spray drying is provided.